semantic change found in traditional song of minangkabau - Edo Lyanwar; Leni Marlina (English Language and Literature, 2018)
This study examine words experience meaning change and types of meaning change in traditional song from Minangkabau. This research intend to find out the words experience meaning change and kind of meaning change on the Minangkabau traditional song lyrics. This research is done based on many people who do not know the meaning of a word in traditional songs of Minangkabau. This research use qualitative descriptive method to analyze data in written form, describe data, and process data based on the existing context in traditional Minangkabau song lyrics. Then, this research use the theory proposed by McMahon (1999). McMahon proposes 4 types of meaning change: extension and restriction, amelioration and pejoration. The data in this research are the lyrics of Minangkabau traditional song. The songs consist of 30 songs. The findings of this study are, there are change of meaning and type of meaning change exist in traditional songs Minangkabau. There are 15 words belong to extension, 2 words belong to amelioration, and 3 words belong to pejoration.